Tenofovir vs. entecavir on recurrence of hepatitis B virus-related hepatocellular carcinoma beyond Milan criteria after hepatectomy. Issue 3 (5th February 2022) - Shen, Junyi; Qi, Weili; Dai, Junlong; Leng, Shusheng; Jiang, Kangyi; Zhang, Yu; Ran, Shun; Li, Chuan; Wen, Tianfu
Abstract: Background: Hepatectomy for hepatocellular carcinoma (HCC) beyond the Milan criteria is shown to be beneficial. However, a high rate of post-operative HCC recurrence hinders the long-term survival of the patients. This study aimed to investigate and compare the impacts of tenofovir (TDF) and entecavir (ETV) on the recurrence of hepatitis B viral (HBV)-related HCC beyond the Milan criteria. Methods: Data pertaining to 1532 patients who underwent hepatectomy and received antiviral therapy between January 2014 and January 2019 were collected from five centers. Recurrence-free survival (RFS) analysis was performed using the Kaplan–Meier method. Cox proportional hazards regression analysis was performed to determine prognostic factors for HCC recurrence. Results: The analysis incorporates 595 HBV-related HCC patients. The overall 5-year RFS was 21.3%. Among them, 533 and 62 patients received ETV and TDF treatment, respectively. The 1-, 3-, and 5-year RFS rates were 46.3%, 27.4%, and 19.6%, respectively, in the ETV group compared with 65.1%, 41.8%, and 37.2%, respectively, in the TDF group ( P < 0.001). Multivariate analysis showed that TDF treatment (hazard ratio [HR]: 0.604, P = 0.005), cirrhosis (HR: 1.557, P = 0.004), tumor size (HR: 1.037, P = 0.008), microvascular invasion (MVI) (HR: 1.403, P = 0.002), portal vein tumor thrombus (PVTT) (HR: 1.358, P = 0.012), capsular invasion (HR: 1.228, P = 0.040), and creatinine levels (CREA) (HR: 0.993, P = 0.031) were statistically significant prognostic factors associated with RFS. Conclusions: Patients with HCC beyond the Milan criteria exhibited a high rate of HCC recurrence after hepatectomy. Compared to the ETV therapy, TDF administration significantly lowered the risk of HCC recurrence.